PENGARUH LINGKUNGAN KERJA, KOMPENSASI, DAN KEPUASAN KERJA TERHADAP KOMITMEN KERJA PEGAWAI KONSULTAN DI WILAYAH SOLORAYA - Sujudi, Imam (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2019)
Work commitment to the organization (organizational commitment) is often a very important issue in the world of work, especially the work commitment of consultant staff in committing to completing work in accordance with the agreement set with the employer organization. The purpose of this study was to determine the effect of the work environment, compensation and job satisfaction both partially and simultaneously on the work commitment of consultant staff in the Soloraya Region. The population in this study were all consultant employees in the Soloraya area, which numbered approximately 50 employees, so that the population was less than 100, the authors took samples, where the entire population was used as research samples, then this study used the census method. The method of collecting data using a questionnaire. Test instruments using validity and reliability tests. Data analysis using classical assumption test, multiple linear regression, t test, F test, and determination coefficient. The results showed partially that the work environment, compensation and job satisfaction had a positive and significant effect on the work commitment of the consultant staff in the Soloraya Region. In addition, simultaneously the work environment, compensation and job satisfaction have a positive and significant effect on the work commitment of the Consultant employees in the Soloraya Region. Thus it can be concluded that the work environment, compensation and job satisfaction partially and simultaneously have a positive and significant effect on the work commitment of the Consultant employees in the Soloraya Region.